1984
DOI: 10.1177/030631284014004004
|View full text |Cite
|
Sign up to set email alerts
|

Science, Society and Politics in Late Nineteenth-Century England: A Further Look at Mechanics' Institutes

Abstract: The need to complement studies of Mechanics' Institutes which are limited to the first half of the nineteenth century with studies of a later period is suggested by showing that Institutes in the north of England, where they were most influential among working-class people, were still very active in the last decades of the century. An analysis of data concerning enrolments in Science and Art classes in Yorkshire Mechanics' Institutes follows, which indicates that working-class people attending these classes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In response to industrialization in the late 1800s, the Royal Society of Arts introduced 'Technical Instruction' in a range of areas alongside educational examinations in 'Technology' (Society of Arts, 1895). The 19th century also saw the growth of Mechanics Institutes (firstly in Glasgow and Edinburgh in the 1820s) -partly designed for the education of the industrial working classes in technology, and partly as enculturation into the idea of progress through the industrialisation of society (see Laurent, 1984). To these can be added the strong tradition in the late 19th and early 20th centuries of workplace apprenticeships and later, of college-based day-release courses for workers.…”
Section: History Of Technological Education In Scotlandmentioning
confidence: 99%
“…In response to industrialization in the late 1800s, the Royal Society of Arts introduced 'Technical Instruction' in a range of areas alongside educational examinations in 'Technology' (Society of Arts, 1895). The 19th century also saw the growth of Mechanics Institutes (firstly in Glasgow and Edinburgh in the 1820s) -partly designed for the education of the industrial working classes in technology, and partly as enculturation into the idea of progress through the industrialisation of society (see Laurent, 1984). To these can be added the strong tradition in the late 19th and early 20th centuries of workplace apprenticeships and later, of college-based day-release courses for workers.…”
Section: History Of Technological Education In Scotlandmentioning
confidence: 99%
“…In these establishments, attendance to science courses was mixed in terms of social class -at least in institutes located in large towns -although working class and lower middle class was the general profile. 100 From the late 1830s, affluent mechanics' institutes such as Liverpool and Manchester, established secondary schools within their premises. The mechanics' institute movement was a useful ally, as it had already established national or regional networks, large libraries and teaching collections, and an early experience in science teaching and textbook production.…”
Section: Secondary Education and The Readerships Of Physics In Englandmentioning
confidence: 99%
“…54 By 1851, there were approximately 700 institutes of various sizes in England, in both towns and "quite small villages." 55 By 1875, the movement was still "vigorous," but toward the end of the century, mechanics' institutes were being replaced by extended elementary schooling, state-supported technical and evening schools, and the increasing availability of libraries, museums, and inexpensive books. 56 In John Laurent's study of the Yorkshire Union of Mechanics' Institutes, founded in 1837, he found that the 109 institutes with approximately 18,000 members in 1850 had grown to 276 institutes with 60,000 members by 1890.…”
Section: Evening Studymentioning
confidence: 99%